Sacred Debts State Civil War Claims and American Federalism - Sinisi, Kyle (The North's Civil War, 2022)
In this innovative book, Kyle Sinisi explores a little-known chapter in the history of American politics-the struggle between states and the federal government over the costs of fighting the Civil War. At stake was the disposition of some 8 million. Focusing on Kansas, Kentucky, and Missouri, Sinisi explores the process by which states were reimbursed by Washington in the most expensive intergovernmental contact of the 19th century. Recasting our understanding of governance, he shows that traditional sources of influence-courts and political parties-were less important in settling claims than adjutants general and private agents who fought for cash bonanzas. These power brokers helped shape the federal bureaucracy-and the process of state building